The Effect of Foreign Exchange Rate, Inflation Rate and Market Return on Return of Bank Perseros’ Stock - Doddi Prastuti; Pristina Hermastuti Setianingrum (Indonesian Journal of Business, Accounting and Management (IJBAM), 2018)
Stock return is affected by many factors, among others are: macro economics environments, political condition, fundamental corporate performance, financial market condition, etc. The purpose of this study is to determine the effect of foreign exchange rate, inflation rate and market return on bank perseros’ stock (government owned banks). We take the case of bank perseros’ because those banks are among the biggest banks in Indonesia in terms of capital. Our observation period starts from January 2010 to September 2014. This period of observation is chosen because it was after the crisis of 2008 and therefore during the time the effect of the crisis on Indonesia’s financial market was mild. Due to the IPO of Bank Tabungan Negara was in the late year of 2009, therefore our period of research run from January 2010 until September 2014.Our justification to use the foreign exchange rate, inflation rate and market return as independent variable is because the foreign exchange rate, inflation rate are considered to be macro economics variable, and market return is financial market variable. The data used in this study is monthly secondary data of stock price data of bank perseros’, the foreign exchange rate, inflation rate and market return. In this study, the independent variables used are the foreign exchange rate (X1), inflation rate (X2) and market return (X3), while the dependent variable used is return of bank perseros’ stock (Y). Result of study shows that the regression function is: Y = - 0.036 + 0.0000033 X1 + 0.046 X2 + 1.531 X3. The test of hypothesis in this study shows that simultaneously the foreign exchange rate (X1), inflation rate (X2) and market return (X3) have significant effect on return of bank perseros’ stock (Y). This is shown by sig. F = 0.000 < 5% (α). Partially the effect of foreign exchange rate and inflation rate on return of bank perseros’ stock are not significant, these are shown by p-value of X1 = 0.468 and p-value of X2 = 0.89 which are greater than α of 5%. Whereas the market return has significant partial effect on return of bank perseros’ stock, the p-value is 0.000. The effect of independent variable on return stock simultaneously is 53.1%. Whereas partial effect of each X1, X2 and X3 is 0.24%, 0.0081% and 52.27% The conclusion of the study is: macro economics and financial markets simultaneously have effect on return of bank perseros’ stock. However the financial market variable has much greater effect compare to the other variables.